Prospects and challenges of Online Banking Services in Pakistan: A case Study of Karachi (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
The current research investigates Prospects and challenges  of Online Banking Services in Pakistan: A case Study of Karachi.Data were collected from 400 respondent using online banking practices in Karachi Sindh-Pakistan by using simple random technique. A structural Questionnaire was developed for the reliability and validity of data.In this study data of independent variable and dependent variable were collect from the customers of different banks of Karachi.It was revealed that the model tested clearly that use of online banking is influenced by channel convenience, perceived risk, security perception, prior internet knowledge and information on online banking. The results also determine that demographic factors also impact significantly on online banking. Finally, this paper suggests that an understanding the factors affecting intention to use internet banking is very important to the practitioners who plan and promote new forms of banking in the current competitive market